THE EFFECT OF USING MIND MAPPING STRATEGY ON THE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Evi Efrilita Sari and Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study investigated the effect of using mind mapping strategy on the students’ achievement in writing procedure text. It was conducted by using experimental research design. The population of this research was grade X students of SMA Negeri 1 Merbau Labura divided into two groups, namely experimental and control group. The experimental group was taught by using mind mapping strategy, while the control group was taught by using lecturing method. The instruments used to collect the data was writing procedure text. After the data were analyzed, it was found that the value of t-observed was 2.764 with the degree of freedom (df)= 58 at the level of significance 0.05. It means that t-observed was higher than t-table (2.764 >2.000). The result of this study showed that teaching procedure text by using mind mapping strategy was higher than that by using lecturing method. It implies that mind mapping strategy is appropriate to be applied for writing procedure text.